SOSIALISASI PERENCANAAN DAN PENGEMBANGAN KARIR SEBAGAI UPAYA MENINGKATKAN MOTIVASI SISWA SMK ATTAUFIQIYYAH DALAM MELANJUTKAN PENDIDIKAN TINGGI DAN BERWIRAUSAHA. - Gede Darma Jata , Anak Agung; Susanto, Denies; Pebriansyah, Pebriansyah (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The purpose of this Community Service Program (PKM) is to implement one of the Three Pillars of Higher Education (Tri Dharma Perguruan Tinggi) and to strengthen the role of universities in providing real contributions to the development and application of knowledge within society. This program was carried out at SMK ATTAUFIQIYYAH Baros with a focus on Career Planning and Development Socialization as an Effort to Increase Students’ Motivation in Pursuing Higher Education and Entrepreneurship. The background of this program lies in the low learning motivation, lack of self-confidence, and limited creativity and career insights among students. These conditions are further exacerbated by external factors, such as entrepreneurship learning that remains theoretical and the lack of family support in encouraging students to continue their education or to develop entrepreneurial initiatives. The methods used in this program were expository, namely verbal material delivery, and inquiry, which emphasizes critical and analytical thinking. These approaches were implemented through lectures, interactive discussions, case studies, entrepreneurship simulations, and practical exercises in career planning. The program targeted 30 students of SMK ATTAUFIQIYYAH and was conducted on October 15–16, 2025. The materials delivered included the importance of career planning, personal potential development, strategies to achieve short- and long-term goals, as well as insights into entrepreneurial opportunities in the digital era. The expected outcomes of this program include an increased understanding among students about the importance of early career planning, higher motivation to pursue tertiary education, and greater confidence in developing simple business ideas. Furthermore, this activity is expected to strengthen the school’s role in producing graduates who are more independent, creative, and competitive in both the workforce and the entrepreneurial sector. Thus, this PKM not only benefits the students but also contributes to the improvement of human resource quality within the school environment and the broader community.